(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The economic empowerment of women is fundamental to achieving gender equity and sustainable development. Women cooperative banks have emerged as key instruments in addressing the financial exclusion faced by women, particularly in rural and semi-urban areas. This study aims to evaluate the impact of various programmes run by women cooperative banks on the economic upliftment of women. The research focuses on savings mobilisation, credit schemes, entrepreneurial support, and financial literacy programmes. Findings reveal that such interventions significantly improve women’s financial independence, income generation, and social participation.